The commandments of Women’s Adornment - Dr. Atiq Ullah; Dr. Abdul Haq (`, 2025)
Islam promotes a balanced approach to beauty and adornment. While it encourages cleanliness, elegance, and taking benefit from Allah’s blessings, it discourages both excessiveness and negligence. Adornment (zeenat) is neither obligatory nor forbidden in Islam, but generally recommended (mustahab), especially when done with modesty and without the intention of showing off. The Prophet Muhammadﷺ valued neatness because Allah loves beauty. Hair care is particularly stressed, with commands to keep it clean and well-groomed. Using wigs made from human hair is prohibited due to deception, but synthetic or wool-based extensions are allowed. Dyeing hair, especially with henna or saffron, is encouraged to differ from Jews and Christians, though black dye is generally discouraged. For women, keeping long hair is part of their adornment. Cutting or shaving it is discouraged unless necessary and some reports of the Prophet’s wives cutting hair are interpreted as acts of simplicity after his death. Women are also allowed to remove unnatural facial hair, like beards or mustaches, as it involves no forbidden imitation. Overall, Islam values beauty with moderation, cleanliness, and sincerity Keywords: Women’s Adornment, Beauty, Cleanliness, Modesty, Neatness